Do Bad Bidders Become Good Targets? - Mitchell, Mark L.; Lehn, Kenneth (Journal of Political Economy, 1990)
This paper empirically examines one motive for takeovers: to change control of firms that make acquisitions that diminish the value of their equity. Firms that subsequently become takeover targets make acquisitions that significantly reduce their equity value, and firms that do not become takeover targets make acquisitions that raise their equity value. Within the sample of acquisition by targets, the acquisitions that reduce equity value the most are those that are later divested either in bust-up takeovers or restructuring programs to thwart the takeover. This evidence is consistent with theories advanced by Marris, Manne, and Jensen concerning the disciplinary role played by takeovers.